The development of posture in very low birthweight infants (<1500 grams) - Magasiner, Vivien Adele (Division of Physiotherapy, 2017)
The aims of the study were to examine postural development in very low birthweight and normal birthweight infants and to determine whether deviant postures were predictive of adverse neurodevelopmental outcome. In the first part of the study the 7 postural responses selected by Vojta to evaluate neuromotor development were applied to 69 very low birthweight (VLBW < 1 500 grams) infants and to 28 healthy full-term infants of normal birthweight (> 2500 grams). Of the 69 VLBW infants, 43 were small for gestational age and 26 appropriate for gestational age. All infants were examined at term and 4 months corrected age. They were all later assessed on the Griffiths Mental Development Scale at 12 and 18 months corrected age. There were significant differences in postural reactions between the 2 groups which confirmed the lower tone and greater extension previously described in VLBW infants. An important finding in the study was that poor head and trunk righting noted at 4 months corrected age in VLBW infants, was associated with less developed locomotion at 12 and 18 months as assessed by the Griffiths Mental Development Scale. Thus, a delay in maturation in VLBW infants which was apparent from the assessment of postural responses was still identifiable on the locomotor sub-scales at 12 and 18 months. Five of Vojta's responses were shown to be useful as part of the neurological assessment of high risk infants. In the second part of the study, the 5 useful Vojta responses were incorporated into the Infant Neurodevelopmental Assessment (INA) which was used to assess 76 high risk VLBW infants. The 76 infants consisted of 34 infants with intracranial lesions on ultrasound and 42 without intracranial lesions. All infants were assessed at term and 4 % months corrected age using the INA. At 12 months corrected age they were all assessed on the Griffiths Mental Development Scale. Six infants were diagnosed as having cerebral palsy, all of whom had intracranial lesions. Several clinical signs indicative of cerebral palsy were significant at 4 % months corrected age and will be useful in future studies to diagnose cerebral palsy early. The association between lack of head and trunk control at 4 % months corrected age and a lower locomotor score at 12 months corrected age proved to be significant again and reinforces the finding that early delay in maturation is identifiable on the locomotor scale at 12 months corrected age.